OKSIDASI TAPIOKA DENGAN HIDROGEN PEROKSIDA DAN KATALISIS IRRADIASI UV C, SERTA APLIKASINYA UNTUK EDIBLE FILM - , ANGELA MYRRA PUSPITA DEWI, Prof. Dr. Ir. Haryadi, M.App.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The pottency of cassava in Indonesia was higher, its production increase every year. The most important part from cassava is starch. Cassava starch is usually applicated in food industry such as for edible film. Edible film from cassava starch has good flexibility but high permeability of water so it should be modified to improve its characteristics with modified cassava starch. Oxidation starch is one of the most important modified starch. This study aims to know the effect of oxidation condition and application of oxidized starch to edible film processing. Ratio starch : liquor, concentration of H2O2, and UVC irradiation time affect to carbonyl and carboxyl content, amylose content, viscosity, swelling power, solubility and degree of whiteness. Carbonyl and carboxyl content decreased with increasing volume liquor. Amylose content, solubility and degree of whiteness increase with increasing volume liquor. Increasing concentration of H2O2,increasing amylose content, solubility and degree of whiteness. Viscosity decrease with increasing H2O2 concentration. Carbonyl content decrease with increasing UV irradiation time. Carboxyl content increase with increasing UV C irradiation time at 10 min and then decrease at 15 min UV irradiation time. Longer time of UV C irradiation time decreasing viscosity, swelling power and degree of whiteness. Condition of oxidation at rasio material : liquor 1:6, 3% H2O2 concentration, and 10 min UV C irradiation gave the highest of edible film. Edible film from oxidized cassava starch has characteristics mositure absorption 29,6%, WVP 0,036 g H2O mm/jam m2, solubility 33,23%, transparency 3,08, dan seal strength 0,035N/m2